The technology of manufacturing double cast or composite cast lamination cylinders - León Delgado, Elard Felipe (2003)
The need in the world market for high-quality laminated products, such as the high productivity of the laminating process, requires increasing the performance levels of laminating cylinders. The rolling cylinder is the main tool or matrix to transform metals and their alloys in the rolling process, which can be hot or cold transformed into products such as bars, squares, profiles, plates, etc. The history of its manufacture is linked to the evolution of the methods used to make iron, steel and other non-ferrous metals. In the last decades there have been several technological advances in the manufacture of laminating cylinders, among which one can distinguish that of double casting or composite casting.